Phytoremediation of Tetracycline and Degradation Products from Aqueous Solutions - Topal, M.; Obek, E.; Senel, Uslu G.; Topal, Arslan E., I (Univ Tehran, 2018)
The present study aims at phytoremediation of Lemna gibba L. in aqueous solutions with different concentrations of TC and Degradation Products (DPs). It also tries to determine whether there are differences in TC, ETC, EATC, and ATC levels, accumulated by Lemna gibba L. Exposure concentrations of 50, 100, and 300 ppb have been selected for TC and DPs, showing that the highest TC50, TC100, and TC300 concentrations in the plant have been 23.5 +/- 1.1, 80.1 +/- 3.9, and 274 +/- 13 ppb, respectively, while the highest ETC50, ETC100, and ETC300 have proven to be 39.5 +/- 1.9, 47.8 +/- 2.4, and 168 +/- 8.4 ppb, respectively. The highest EATC50, EATC100, and EATC300 concentrations in the plant have been 45.3 +/- 2.3; 65 +/- 3.0 and 173 +/- 9.0 ppb, respectively, whereas the highest ATC50, ATC100, and ATC300 concentrations in Lemna gibba L. have been 34.7 +/- 1.7, 39.6 +/- 0.2, and 114 +/- 5.6 ppb, respectively. TC, ETC, EATC, and ATC concentrations in Lemna gibba L. have increased with the increase of initial TC, ETC, EATC, and ATC concentration.
Keywords: Antibiotics; duckweed; Lemna gibba L.; metabolites